Site management and productivity in tropical plantation forests: Proceedings of Workshops in Piracicaba (Brazil) 22-26 November 2004 and Bogor (Indonesia) 6-9 November 2006 - Nambiar, E.K.S. (Center for International Forestry Research, 2008)
These proceedings present results from research done for a decade in the CIFOR project Site Management and Productivity in Tropical Plantations. They include papers presented at a workshop in Brazil in November 2004 and then updated at a workshop in November 2006 at Bogor, Indonesia. These papers complement the proceedings in the series published by CIFOR in 2004, 2000, and 1999. Currently the research network includes 16 sites in 8 countries representing a range of biophysical environments, species, productivity potentials and management strategies. Research is focused on inter-rotation site management. Good management of this phase, between harvesting and tree establishment in the next rotation, is critical for the future outcome of plantations. During this phase, there is potential for soil degradation, but also opportunities to introduce sound new technologies to improve long-term productivity and soil properties. Although the species, the site, and soil problems vary according to local conditions, all experiments are designed to provide knowledge that will benefit all plantation growers and our understanding of the underlying processes which enable us to increase and sustain plantation productivity with environmental care.